Revitalization of the Execution of Religious Court Decisions through Engineering Compliance with the Implementation of Execution of Judgments Related to the Fulfillment of the Rights of Ex-Wives and Children - Agus Digdo Nugroho; Atma Suganda; Sirajuddin Sailellah (Ridwan Institute, 2023)
The implementation of religious court rulings related to the fulfillment of the rights of former wives and children has many obstacles that cause very few rulings to be successfully implemented. The existence of regulations governing the execution of existing rulings is quite outdated because it is still based on the regulations left by the Dutch East Indies Colonial. Breakthroughs in the field of execution such as dwangsom or delays in the pronunciation of talaq pledges to pressure the convicted have not shown significant and optimal results in overcoming this problem. Ideas emerged on opportunities for advances in information technology and integration of population administration that can be used to engineer compliance with the implementation of rulings in realizing the fulfillment of the rights of former wives and children after divorce. The research method used is normative juridical with a legal approach, case approach, historical approach, comparative approach, and conceptual approach. The theories used include Authority Theory as Grand Theory, Legal Protection Theory as Middle Range Theory, and Legal Theory that Engineers Society as Applied Theory. The results of the study are the regulation of the Supreme Court of the Republic of Indonesia regarding the execution of religious court decisions in the implementation of decisions related to the rights of former wives and children after divorce contained in laws and regulations both materially and formally as well as policy regulations. The existence of this legal basis has not been able to effectively guarantee the fulfillment of the rights of former wives and children after divorce. Strengthening the execution of religious courts needs to be carried out as a renewal that is able to overcome the problem of stagnant executions that exist today, especially the existing executions are still unable to be carried out simply, quickly, and at low cost. Strengthening the authority to implement decisions related to the rights of former wives and children by religious courts through the suspension of citizens' rights to the convicted is carried out by utilizing the development of information technology and the integration of population databases to improve compliance and successful execution of religious court decisions. Social engineering by marrying law and information technology will be able to strengthen the authority to carry out executions by religious courts so as to create legal protection that is certain and fair for ex-wives and children after divorce.